If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = 4x + -8 Reorder the terms: 28 = -8 + 4x Solving 28 = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 28 + -4x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 28 + -4x = -8 + 0 28 + -4x = -8 Add '-28' to each side of the equation. 28 + -28 + -4x = -8 + -28 Combine like terms: 28 + -28 = 0 0 + -4x = -8 + -28 -4x = -8 + -28 Combine like terms: -8 + -28 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| 2x+12-x=9+3x-7 | | 4x-(x-7)=10 | | 12=2t+6-14 | | x^3+4x^2-5x-20=0 | | 6=11v-5v | | 3=2187 | | 63=4v+3v | | -5-16+16=9 | | 45=11-2j+50 | | -4(-8y+5)-7y=7(y-3)-2 | | 45=112j+50 | | 5(4.5+0.5y)-2=18 | | 2x-7=1x+9 | | (-6c+5)-(-3c+8)= | | 8y^2+2y-36=0 | | 4(x-1)=10x+20 | | 8y+2y-36=0 | | -40-7+9x=14 | | 3y+2y=4 | | f(x)=10x-2 | | 18x+9=5x+100 | | f(x)=10x-2graph | | 5x-2(-2x-9)=18 | | Y-6=-1(x+7) | | -25=87-8x | | (3x^2+2x)+(3x^2-2x)= | | f(x)=2x-4graph | | 3(x+4)-x=24+x | | t-2=-3t+4 | | Y-8=-1(x+12) | | 1/3*2/5=34 | | 60=3x-2y |